KONSEP PENDIDIKAN KARAKTER MENURUT KI HAJAR DEWANTARA - Ani Setyorini; Siti Asiah (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2021)
Character is an important thing that must exist in every human being. Because humans who havecharacter will be able to bring themselves to participate actively in society and be able to contributeto the development of the nation and state to be more advanced. In addition, good character canlead a person to have a good personality and also be useful for the people around him. This thesisaims to determine the concept of character education according to Ki Hajar Dewantara. As we knowthat Ki Hajar Dewantara is a national education figure and is known as the Father of Education.This thesis uses a qualitative descriptive approach and the type of research used is library research.This research is sourced from primary and secondary data sources. Primary data is the main andimportant data that is directly related to the thoughts of the characters. The primary data sourcecomes from the book by Ki Hajar Dewantara. While secondary data is an indirect source of data,in the form of library materials that have the same study produced by other thinkers. The secondarydata comes from books, journals and articles related to character education according to Ki HajarDewantara. The data collection technique is carried out by collecting data from the exploration oflibrary materials both from primary and secondary data sources which are studied holistically, thenanalyzed based on a certain framework of thinking or theory/philosophical paradigm that underliesit, while the data analysis used is content analysis ( content analysis). The results of this study can beconcluded that the concept of character education according to Ki Hajar Dewantara is a concept thatuses an approach to the soul of the learner, without going through coercion and based on the nature ofnature. Ki Hajar Dewantara’s concept of character education focuses on character education in threeeducational centers, namely the family realm, the education realm, and the youth movement realm.As well as using materials that are adapted to the age level of students, and using a method known asthe Among system which consists of Momong, Among and Ngemong. This character education aims tomake students become independent human beings physically and mentally